Mesothelin (MSLN) methylation and soluble mesothelin-related protein levels in a Chinese asbestos-exposed population - Yu, Min (Environ Health Prev Med, 2015)
OBJECTIVES: This study investigated the mesothelin (MSLN) methylation and its relationship with soluble mesothelin-related protein (SMRP) levels in participants stratified by asbestos exposure scenarios and benign asbestos-related diseases (ARDs). METHODS: The presence of benign ARDs was confirmed through chest X-ray and the asbestos exposure history was obtained using a standardized questionnaire in this study, including 262 participants. Sera SMRP were measured using MESOMARK, and MSLN methylation in genomic DNA extracted from whole blood was detected by real-time methylation-specific PCR. Covariates were compared with SMRP concentrations using correlation analysis and the potential covariates affecting SMRP were determined by multiple linear regression analysis, and the distribution of methylation status was analyzed by Chi-square test. RESULTS: There was a trend toward elevation of SMRP values in healthy individuals exposed to asbestos as compared with those without asbestos exposure. The highest median level of SMRP was 1.3 nM in subjects with asbestosis, followed by cases with pleura plaque and asbestosis (1.2 nM), pleura plaque (0.9 nM), healthy subjects with occupational exposure (0.9 nM), non-occupational exposure (0.8 nM), and mixed exposure (0.8 nM). Within asbestosis cases, those with higher profusion scores had higher SMRP values than those with lower profusion scores (1.6 vs. 0.8 nM). Based on multi-regression analysis, the trend toward elevation of SMRP remained significant in subjects with occupational exposure or in those with asbestosis, as compared with healthy subjects without exposure (p < 0.01), although body mass index had an effect on SMRP (p < 0.0001). Regardless of the differences in SMRP levels among these subgroups, MSLN methylation ranged from 80.5 to 92.5 %, with no significant difference. The elevated level of SMRP in asbestosis with higher profusion scores could not be attributed to low MSLN methylation status. CONCLUSIONS: Our findings suggest that the elevation of SMRP is related to asbestos exposure and benign ARDs especially for cases with high profusion scores, which is independent of MSLN methylation.